2000
DOI: 10.1097/00005768-200006000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Maximal aerobic power, lactate threshold, and running performance in master athletes

Abstract: The results of this study demonstrate that VO2max (mL x kg(-1) x min(-1)) is a better predictor of performance than LT in older male and female runners. Additionally, LT as a percentage of VO2max increases significantly with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 11 publications
3
50
2
1
Order By: Relevance
“…Despite the evidence that men and women age similarly in the physiological factors that influence endurance performance (Joyner 1993;Wiswell et al 2000), several investigations have found that sex differences in marathon performance increase with advancing age (Hunter and Stevens 2013;Lepers and Cattagni 2012). The present investigation indicated that female participants obtained a running time in the marathon <20 % higher than male participants of the same age.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Despite the evidence that men and women age similarly in the physiological factors that influence endurance performance (Joyner 1993;Wiswell et al 2000), several investigations have found that sex differences in marathon performance increase with advancing age (Hunter and Stevens 2013;Lepers and Cattagni 2012). The present investigation indicated that female participants obtained a running time in the marathon <20 % higher than male participants of the same age.…”
Section: Discussioncontrasting
confidence: 76%
“…Before or after this age range, endurance running performance decreases. While it is well established that aging progressively reduces VO 2max while the lactate threshold as a percentage of VO 2max and running economy are probably unaffected by this process (Tanaka et al 1997;Wiswell et al 2000;Quinn et al 2011), it is unclear why younger marathon participants obtain a decreased performance, in comparison to the age of maximal performance. Figure 1 suggests the existence of a "maturation" process for marathon performance, although this effect might be related to training (young athletes typically compete over shorter distances) rather than a biological explanation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well-established that maximal oxygen uptake (V O2max) is an important physiological variable given it sets the upper limit for aerobic metabolism [1] and predicts endurance performance amongst untrained groups [2,3] . However, in a highly-trained population (i.e.…”
Section: Introduction To the Research Problemmentioning
confidence: 99%